Measures To Develop the Ability To Self-Study Chemistry For High School Students With the Support of AI Chatbot - Nguyen Minh Giam; Nguyen Van Doc; Nguyen Thi Hoai Nam; Nguyen Thi Huong Giang; Ngo Tu Thanh (Journal of Education For Sustainable Innovation, 2023)
AI Chatbot is applied in most areas of life, in the field of education, AI Chatbot is also a term that many educators and teachers are interested in researching and applying. The most application of AI Chatbot in education is in teaching, AI Chatbot helps teachers make teaching work easier, saving more time. Besides, the development of self-study capacity is also a matter of concern in order to equip the necessary qualities and skills for an independent learner with a spirit of lifelong learning. The article presents measures to develop the ability to self-study Chemistry with the support of AI Chatbot for junior high school students. Thereby, teachers have orientations for building teaching scenarios to help students self-study and be autonomous in their learning when learning with AI Chatbot. With the benefits that AI Chatbot brings, learning with the support of AI Chatbot needs to be used not only in a specific subject or grade level, but should be used widely at all levels and for students. different subjects.